Validación de un instrumento para evaluar conocimientos, actitudes y practicas en diagnostico cefalometrico en ortodoncistas (2023)
Validity refers to the metric quality criterion about the adequacy and interpretation of the pressures of the instrument in terms of the construct that it claims to measure. The objective of this study was to validate an instrument to evaluate the C.A.P in the cephalometric diagnosis in orthodontists. An instrument made up of 28 items categorized into 3 dimensions (knowledge, attitudes and practices) of dichotomous type on cephalometric diagnosis in orthodontists was validated.